2022
DOI: 10.1002/ptr.7411
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology reveals potential functional components and underlying molecular mechanisms of Andrographis paniculata in esophageal cancer treatment

Abstract: Antitumor and antimetastatic effects of the medicinal herb Andrographis paniculata (AP) in esophageal cancer (EC) have been previously reported. In this study, we aimed to uncover the potential functional components and the underlying molecular mechanisms of AP in EC treatment using network pharmacology and experimental validation. Twenty-two potential active AP compounds against EC were revealed, including the antitumor/antiinflammatory compounds panicolin, moslosooflavone, and deoxyandrographiside. Epidermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The active components in APW, bisandrographolide A, and bisandrographolide C, were shown to have high affinity to CD81 and could downregulate the expression of CD81 in esophageal cancer cells and tumors in mice models (Yue et al, 2022). Last but not least, another two potential active components (panicolin, moslosooflavone) of APW have been validated to be responsible for the downregulation of expression of metastasis‐related targets (e.g., EGFR , STAT3 , and AKT ) in esophageal cancer cells (Cheung, Yue, Gomes et al, 2022). All these findings elucidated the underlying mechanism of action of AP, which could in turn support the efficacy of AP observed in patients in the present clinical study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active components in APW, bisandrographolide A, and bisandrographolide C, were shown to have high affinity to CD81 and could downregulate the expression of CD81 in esophageal cancer cells and tumors in mice models (Yue et al, 2022). Last but not least, another two potential active components (panicolin, moslosooflavone) of APW have been validated to be responsible for the downregulation of expression of metastasis‐related targets (e.g., EGFR , STAT3 , and AKT ) in esophageal cancer cells (Cheung, Yue, Gomes et al, 2022). All these findings elucidated the underlying mechanism of action of AP, which could in turn support the efficacy of AP observed in patients in the present clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, microarray analysis revealed that multiple genes related to intercellular adhesion and metastatic processes, such as Int1 proto-oncogene (WNT, nuclear factor kappa B (NF-kB), and ErbB (gene symbol for epidermal growth factor receptor family) signaling pathways were regulated by AP water extract in esophageal cancer cells (Li et al, 2018). Our recent network pharmacology analysis verified that APW could modify the expressions of epidermal growth factor receptor (EGFR), signal transducer and activator of transcription 3 (STAT3), RAC-alpha serine/threonine-protein kinase (AKT1), prostaglandin G/H synthase-2 (PTGS2), chemokine (C-X-C motif) ligand 8 (CXCL8), phosphatidylinositol 4,5-bisphosphate 3-kinase subunit alpha (PIK3CA), and toll-like receptor 4 (TLR4) in esophageal cancer cells (Cheung, Yue, Gomes, et al, 2022). The combined treatments of AP with chemotherapeutics in mice also exhibited beneficial efficacies without observable side effects (Yue et al, 2015(Yue et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…To get more evidence that protection of primary cilia prevented SMG-induced oxidative stress and loss of osteogenic potential of osteoblasts, we screened for compounds with the ability to protect the primary cilia against SMG in our lab. One of the natural compounds we obtained is MLF (Figure 7b), a flavonoid isolated from Mosala soochowensis Matsuda, Elsholtzia blanda, and Andrographis paniculata, and has been reported to possess antioxidant, anti-inflammatory, and antitumor activities (Chao et al, 2010;Cheung et al, 2022;Wu et al, 1982). As shown in Figure 7a, the dot-like primary cilia in the SMG group became longer in dose-dependent manner in the SMG + MLF groups and the longest cilia (longer than that of NG group) were obtained by MLF supplementation at the concentration of 10 −6 mol/L F I G U R E 6 Effects of miR-129-3p overexpression on the redox homeostasis and osteogenic potential of rat calvarial osteoblasts (ROBs) exposed to simulated microgravity (SMG) or normal gravity (NG) control.…”
Section: Mlf Prevented Smg-induced Shortening/ Disappearance Of Prima...mentioning
confidence: 99%
“…The metabolome is located downstream of the gene regulation network and protein interaction network, and metabolomics studies are only conducted for potential metabolites and their related metabolic pathways, and thus lacking further exploration of their direct relationships. In contrast, network pharmacology is a novel research method focusing on upstream based on database mining and bioinformatics theory, which can link components, targets and pathways [24][25][26][27][28] . Network pharmacology is conducive to the in-depth study of pharmacodynamically active ingredients and mechanisms of action in traditional Chinese medicine.…”
mentioning
confidence: 99%